The Comparison of Dynamic Balance in Female Futsal Players with and Without Patellofemoral Pain Syndrome - negar kourosh fard; mohamad hossein alizade; sedighe kahrizi (Sport Sciences and Health Research)
The purpose of this research was to compare dynamic balance in two groups of female futsal players with and without patellofemoral pain syndrome (PFPS). A comparative method was used in this research and the subjects included 30 genius female futsal players. 15 subjects suffered from PFPS with pain duration of 11.26±7.65 months and age of 21.73±1.83 years old, and 15 subjects who did not have PFPS with age of 21.46 ± 2.77 years old. Two groups had no significant differences in their height, weight and BMI (P>0.05). DPC (dynamic postural control) was measured by Biodex system at two instability levels of low (6) and high (3). DPC indices were total (TL), anteroposterior (APL) and mediolateral (MLL). Data were compared by independent t-test between the two groups. Results showed significant differences in all three DPC indexes at level (6) between groups (TL (P=0.03), APL (P=0.02), MLL (P=0.05)) so that the comparison of the means between the two groups revealed higher balance sway in PFPS group at level (6). But at level (3), in spite of higher mean of balance sway in PFPS group, no significant differences were observed between the two groups. This research showed some DPC disorders in female futsal players with PFPS and anterior knee pain. But this balance disorder depends on the amount of instability and DPC demands in different environmental conditions. In more stable conditions in which demands of postural control are closer to static conditions, balance reaction of PFPS group is lower than control group. But in more instable conditions which are closer to dynamic condition, balance reaction of PFPS group is more similar to the control group. Finally, it seems that more investigation is necessary to understand postural control reactions and to assess the relationship between anterior knee pain and DPC at other instability levels.